Studi Tingkat Efisiensi: Perbandingan Besar Perusahaan dan Efek Krisis Ekonomi - Hakim, Lukmanul (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
The purpose of this study are (I) to analyze the efficiency differences between large and small firms. and (2) to analyze the impact of monetary crisis to efficiency, both large and small firms_ All the manufacturing firms listed on the JSX are ranked by total assets. The 30 highest firms are categorized as the large firms and the 30 lowest firms are categorized as the small firms. Data taken from the Indonesian Capital Market Directory 1999. Six financial ratio are used to represent the company efficiency. Those ratios are consist of three categories: profitability, liquidity and operation. and leverage. In general, the result of the study suggest that large and small firms have their own efficiency niches. There are no differences between large and small firms with regard to efficiency. In addition, consistent with Machfoedzs (1999) study. company efficiency are impacted by economic crisis. and the large firms are more impacted by economic crisis than the small one.